Actions to promote circular economy: case study of multinational manufacturers in the automotive and fast-moving consumer goods in Mexico - Loza Hernandez, Lourdes; Arroyo, Pilar (Acta Universitaria, 2023)
The overuse of natural resources as manufacturing inputs demands enterprises to support sustainable development through a transition from a linear model of production to a circular and resource-efficient model. This work applies a multiple-case research design based on secondary information to explore the advancement of circular economy (CE) among six subsidiaries of multinationals that operate in Mexico. The qualitative analysis shows that reduction of natural resources and closing the loop of water, followed by closing the package cycle and using renewables, are the main approaches applied by companies in the automotive and fast-moving consumer goods sectors. Slowing the product life cycle and closing the supply chain are the least used approaches. Results show a limited advancement in the implementation of circular economy models and provide guidelines to other companies as well as recommendations for the establishment of a legal framework that complements the bottom-up efforts of enterprises located in a developing country.